God interrupted : heresy and the European imagination between the world wars - Lazier, Benjamin 1971- (Princeton Univ. Press, 2012)
Could the best thing about religion be the heresies it spawns? Leading intellectuals in interwar Europe thought so. They believed that they lived in a world made derelict by God's absence and the interruption of his call. In response, they helped resurrect gnosticism and pantheism, the two most potent challenges to the monotheistic tradition. In God Interrupted, Benjamin Lazier tracks the ensuing debates about the divine across confessions and disciplines. He also traces the surprising afterlives of these debates in postwar arguments about the environment, neoconservative politics, and heretical forms of Jewish identity. In lively, elegant prose, the book reorients the intellectual history of the era. God Interrupted also provides novel accounts of three German-Jewish thinkers whose ideas, seminal to fields typically regarded as wildly unrelated, had common origins in debates about heresy between the wars. Hans Jonas developed a philosophy of biology that inspired European Greens and bioethicists the world over. Leo Strauss became one of the most important and controversial political theorists of the twentieth century. Gershom Scholem, the eminent scholar of religion, radically recast what it means to be a Jew. Together they help us see how talk about God was adapted for talk about nature, politics, technology, and art. They alert us to the abiding salience of the divine to Europeans between the wars and beyond--even among those for whom God was long missing or dead.